(3GdWHbGJ GdcHQis - (3eMeO Hf SYO Hf efjY GdRgQj, CHh YHO Gddg cGJH GdhGbOj, GHf SYO , J (B230 (3g` s
(3ChdgG (B:s
(3aj PcQ eG oMHH Edi QShd Gdg ef GdfSGA hGdWjH s
(3BNQgG (B:s
(3aj ZRhI GdCHhGA s
(3GdLRA GdKGdK ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B21s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B280 s
Keywords: (3GdJGQjNs